Analysis of Students' and Parents' Perceptions of Self-Confidence in Learning at Gadang IV Public Elementary School in Malang City - Ani, Yulianti; Susanti, Romia Hari; Iswahyudi, Didik; Pedi, Afrensia R. Jola; Prasetyaningtyas, Rani (Universitas Islam Lamongan, 2025)
This study aims to describe the results of an analysis of fourth-grade students' and their parents' self-confidence in the 2024/2025 academic year. Data analysis was conducted using a self-confidence survey questionnaire completed by students, and the results revealed parents' views on their children's levels of self-confidence in the context of learning in elementary school. The study employed a qualitative descriptive design incorporating a survey as the primary data collection instrument. It involved 56 fourth-grade students and their 56 parents. Data collection was conducted using a self-confidence questionnaire validated using a Likert scale. The results of the analysis of student self-confidence indicators included the ability to understand material (85%), the courage to express opinions (75%), readiness to face challenges (80%), and cooperation in groups (75%). Meanwhile, the results of the questionnaire on parents' confidence in accompanying their children's learning were 79.38%, openness to receiving advice from teachers or the school was 84.17%, and role modeling to foster children's self-confidence was 80.83%. These data show that both parents and students have relatively high levels of self-confidence. However, there are variations in students' confidence in expressing opinions and in parents' ability to support their children's learning. These findings confirm that collaboration between parents and students can build children's self-confidence and play a strategic role in learning success in elementary school.